Therapeutic potential of plant-derived natural products against drug-induced liver injury - Chen, Yan; Mei, Yu-Qi; Hou, Lin; Li, Ke-Jian (Frontiers in Pharmacology, 2025)
Drug-induced liver injury (DILI) is a major cause of drug development failure and post-marketing restrictions. To date, over 1,000 drugs have been reported to cause liver damage, such as acetaminophen, isoniazid, methotrexate, triptolide and so on. However, there are currently no effective therapies for DILI. Plant-derived natural products including flavonoids, phenylpropanoids, terpenoids, and glycosides have been used for the treatment of DILI due to their low toxicity and strong bioactivity. These anti-DILI compounds involve multiple mechanisms, such as reducing oxidative stress and inflammation, restoring mitochondrial function, and suppressing apoptosis. This review primarily summarizes the recent advances over the past 5 years in the therapeutic potential of natural products against a range of commonly used hepatotoxic drugs rather than focusing on a specific hepatotoxic agent. The insights will provide a cue for further research and promote the development of novel and effective drugs for treating DILI.